2023
DOI: 10.21203/rs.3.rs-3128881/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The influence of job burnout on quiet quitting among nurses: the mediating effect of job satisfaction

Abstract: Introduction: Quiet quitting seems to be a new threat for healthcare workers and organizations. Individuals now tend to stay at their jobs covering only the bare requirements. High levels of burnout among nurses especially after the COVID-19 pandemic could further increase their levels of quiet quitting. Objective: To investigate the impact of nurses’ job burnout on their quiet quitting. Moreover, we assessed the mediating effect of job satisfaction on the relationship between burnout and quiet quitting. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The above three situations experienced by nurses have a negative impact on them, affecting their physical and mental well-being as well as their performance. Musculoskeletal problems, severe sleep disturbances, depression, and anxiety, reduced work capacity, social support, and control of work, as well as increased emotional stress, quiet quitting, and work time, make up the effects of the above factors on nurses [ 71 , 72 , 73 ]. In many cases, stress, burnout, and post-traumatic stress disorder are correlated among themselves, and the presence and increased level of one feeds into the others, creating a highly stressful and particularly unhealthy work environment [ 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above three situations experienced by nurses have a negative impact on them, affecting their physical and mental well-being as well as their performance. Musculoskeletal problems, severe sleep disturbances, depression, and anxiety, reduced work capacity, social support, and control of work, as well as increased emotional stress, quiet quitting, and work time, make up the effects of the above factors on nurses [ 71 , 72 , 73 ]. In many cases, stress, burnout, and post-traumatic stress disorder are correlated among themselves, and the presence and increased level of one feeds into the others, creating a highly stressful and particularly unhealthy work environment [ 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a large percentage of nurses are quiet quitters and they choose quiet quitting more often than other health care professionals (Galanis, Katsiroumpa, Vraka, Siskou, Konstantakopoulou, Katsoulas, Moisoglou, et al, 2023a). Nurses job burnout is a positive predictor of quiet quitting, while job satisfaction is a negative one of quiet quitting (Galanis, Katsiroumpa, Vraka, Siskou, Konstantakopoulou, Katsoulas, Moisoglou, et al, 2023b). Due to the pandemic, nding a job is di cult.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nurses during the pandemic experienced high rates of emotional and physical burnout, as well as depersonalization (Galanis et al, 2021. Additionally, during the COVID-19 pandemic, a new emergence have emerged among healthcare workers and especially nurses: the phenomenon of quiet quitting (Galanis et al, 2023c(Galanis et al, , 2023d. In this context, the phenomenon of quiet quitting has emerged, which threatens not only the well-being of workers but also the survival of countries' economies worldwide, as it leads to reduced productivity.…”
Section: Introductionmentioning
confidence: 99%